The Moral Teachings of Serat Papali and Their Implications for Strengthening Character Education in Indonesian Senior High Schools - Hafidzatuz Zuhriatin Awalin; Wahyudi Siswanto; Dwi Sulistyorini (FKIP - Universitas Riau, 2026)
This study investigates the moral teachings of Serat Papali and their implications for strengthening character education in Indonesian senior high schools. The research is motivated by the need to integrate local wisdom into modern educational frameworks to address challenges in developing students’ moral, social, and cognitive competencies. The study employs a qualitative content analysis method, examining the text of Serat Papali to identify ethical values and their relevance to the eight dimensions of the Senior High School Graduate Profile. The findings reveal that the text provides a coherent moral framework through three main pillars: self-ethics, including reflection, humility, and inner discipline; social ethics, emphasizing harmony and mutual respect; and ethics toward God, representing spiritual maturity. These values contribute to enhancing critical thinking, autonomy, collaboration, citizenship, creativity, productivity, well-being, and ethical communication among students. The study concludes that integrating Serat Papali into formal curricula can strengthen students’ character development while preserving cultural identity, offering a sustainable and contextually relevant approach to character education. The research also suggests future studies to explore practical strategies for curriculum integration and to assess the impact of these ethical teachings on student behavior and learning outcomes in diverse educational settings.